Effect of the Subtropical Jet Stream over the rain variability in the Syrian coastal region in summer - Issa , Maryam; Amalla, Ali (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study was conductedin 2016 to see the impact of the jet stream over on variations the tropical rain in the regionof the Syrian coast,and has daily and monthly observation of the site by the current virtual movement of the sun, and the accompanying withdrawal of air masses to the surface, causing a state of atmospheric stability,and therefore studded a private air depressions during the summer half of the year, and studied each of the geographical location of the regionand the astronomical research of the impact in the face of Western wind.It was synoptic uppeweather maps r analysis at 200mbr, and turned out to be the focus of mainstream role in incitementof air masses, and identified the relationship between the atmospheric pressure values at 200mbr, and the amount of rainfall, where the relationship is an inverse to the level of the month and quarter and year.